Treating Children with ASD: The Perspective of Caregivers - Noor Breik; I fan Kuo; Shawn Bugden; Michael Moffat; Silvia Alessi-Severini (Frontiers Media S.A., 2018)
Purpose: Treatment of Autism Spectrum Disorders (ASD) is challenging. Parents/caregivers' perspective on the effectiveness of therapies and services available to their children is important but neglected in the literature on ASD.  This study investigated such perspective through questionnaire-guided interviews with a group of parents in the province of Manitoba (Canada). A secondary objective of the study was to explore how health care professionals and specifically pharmacists can assist in providing better care to children with ASD.  Methods: Informed consent was obtained from all participants. Data on diagnoses and prescribed medications were collected from medical charts. Parents/caregivers completed questionnaires during interviews scheduled at their convenience. Specific questions were asked to gather caregivers/parents' perspectives on the effectiveness of medications and non-pharmacological interventions in controlling symptoms experienced by their children.  Information on access to education and health services was also assessed. Common themes were identified using thematic analysis. Results: All children attended school, 88% were males, 50% experienced eating/sleeping difficulties; 69% reported Attention Deficit Hyperactivity Disorder comorbidity. Risperidone was reported to be effective in controlling aggressive behaviours. Methylphenidate and aripiprazole were often discontinued. Melatonin and occupational therapy services were said to be very useful. Access to behavioural therapy was often limited. Parents were concerned about lack of trained professionals in schools, limited understanding of their children's needs, and uncertainty for the future. Conclusions: Better education and awareness are necessary to help ASD children and their families. Pharmacists should explore opportunities to provide better services.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.